Pendekatan Adaptif Terapi Seni Untuk Pemulihan Psikososial Siswa Pascabencana Di Bireuen - Ichsan Ichsan; Asrinaldi; Indra Setiawan; Nadra Akbar Manalu; Teuku Muhammad Husni (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2026)
This community service study examines an adaptive art-therapy approach combining doodle drawing and dance to support students’ psychosocial recovery in post-disaster contexts. The program was implemented over two days in two schools in Bireuen—MTSN 2 and MAN 7—with 140 participants divided equally into drawing and dance groups. Methods included guided repetitive doodle exercises (non-representational lines and color exploration), movement-based dance sessions, and adaptive facilitation through motivation and ice-breaking for low-engagement groups. Data were collected through structured observation using three indicators: participation, positive emotional expression, and expressive courage. Results show higher baseline engagement at MTSN 2 (participation 88%; positive affect 85%; expressive courage 82%). At MAN 7, initial engagement was low (52%; 48%; 45%), but improved substantially after adaptive intervention (78%; 75%; 72%). Findings indicate that art-based interventions are effective for psychosocial recovery, while adaptive facilitation significantly enhances outcomes in low-motivation contexts. The study highlights the importance of flexible, context-sensitive strategies in community-based psychosocial programs.